Applications of the CRISPR-Cas9 system in cancer biology - Sánchez-Rivera, Francisco J. (Nat Rev Cancer, 2015)
The prokaryotic type II clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 system is rapidly revolutionizing the field of genetic engineering, allowing researchers to alter the genomes of a large variety of organisms with relative ease. Experimental approaches based on this versatile technology have the potential to transform the field of cancer genetics. Here we review current approaches based on CRISPR-Cas9 for functional studies of cancer genes, with emphasis on its applicability for the development of the next-generation models of human cancer.